A rise in saliva and urine pH in children with SCN1A-related epilepsy: An exploratory prospective controlled study - Lu, Qian; Wang, Yang-Yang; Chen, Hui-Min; Wang, Qiu-Hong; Yang, Xiao-Yan; Zou, Li-Ping (Frontiers in Neurology, 2022)
Objective SCN1A, encoding the alpha 1 subunit of the sodium channel, is associated with a range of related epilepsy. This study aims to assess saliva and urine pH in children with SCN1A-related epilepsy. Methods A prospective controlled observational study with a 1:1 ratio was conducted on seven patients with SCN1A-related epilepsy and seven healthy children of the same family, gender, and age but without a history of seizures. The pH of saliva and urine was measured by pH test paper. Parents of patients with epilepsy recorded seizures to compare the relationship between pH and seizures. Results The fourteen participants were all males, aged 1 to 14 years. Seven patients had different pathogenic SCN1A variants. The pH of saliva and urine was monitored for 21–95 days. The pH of saliva and urine was higher in patients with SCN1A-related epilepsy than in the healthy group. The urine pH in Dravet syndrome patients was high compared with other epilepsy patients. The urine pH in patients with seizures was higher than that in patients without seizures, which occurred during the study. Conclusions The pH of saliva and urine was chronically high in patients with SCN1A-related epilepsy, and urine pH was higher in patients with seizures and with Dravet syndrome.